2023
DOI: 10.1007/s10552-023-01703-0
|View full text |Cite
|
Sign up to set email alerts
|

Barriers and facilitators to effective cervical cancer screening in Belize: a qualitative analysis

Abstract: Purpose Belize has among the highest cervical cancer incidence and mortality rates of Latin American and Caribbean countries. This study evaluates the perspectives of key stakeholders for cervical cancer screening in Belize and identifies the barriers and facilitators for providing equitable access to prevention services. Methods Semi-structured interviews discussing cervical cancer screening were conducted with key stakeholders across the six districts of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
1
0
0
Order By: Relevance
“…In high-income countries, low screening coverage is related to current health and social inequalities [ 38 ]. Our results on the association between SES and CC screening behaviors reflect the literature [ 14 , 39 , 40 ]. Specifically, we found that SES disparities were more strongly associated with Pap smear screening uptake in Réunion than in mainland France, irrespective of culture and religion.…”
Section: Discussionsupporting
confidence: 90%
“…In high-income countries, low screening coverage is related to current health and social inequalities [ 38 ]. Our results on the association between SES and CC screening behaviors reflect the literature [ 14 , 39 , 40 ]. Specifically, we found that SES disparities were more strongly associated with Pap smear screening uptake in Réunion than in mainland France, irrespective of culture and religion.…”
Section: Discussionsupporting
confidence: 90%